Transforming surface coordination polymers into covalent surface polymers: linked polycondensed aromatics through oligomerization of N-heterocyclic carbene intermediates - Matena, Manfred; Riehm, Till; Stöhr, Meike; Jung, Thomas A.; Gade, Lutz H. (Angewandte Chemie. International edition, 2008)
Isomerize and polymerize! Thermally induced tautomerization of the N-heteropolycyclic 1,3,8,10-tetraazaperopyrene to a Wanzlick-type carbene intermediate on a Cu(111) surface leads to covalently linked polyaromatic chains, which can be mechanically manipulated. The pictures show the respective structures superimposed on the STM images.
Gesehen am 15.12.2022